THE VILLAGE-OWNED ENTERPRISE “KITA” STRATEGY TO ACCELERATE THE IMPLEMENTATION OF FINANCIAL MANAGEMENT PRINCIPLES - Aprina Nugrahesthy Sulistya Hapsari; Intiyas Utami; Yohanes Yakobus Werang Kean (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
BUMDes is one of the government's goals in restoring the Indonesian economy, as stated in the Village SDGs. However, the findings show that there are still many BUMDes that cannot answer the government's expectations and instead commit fraud in the management of BUMDes funds. This study aims to see from the point of view of the implementation of principles in the financial management of BUMDes, what is the strategy of BUMDes in realizing harmony with the Village SDGs, especially in the goal of recovering the Indonesian economy? The main object of this research is BUMDes